Organochlorine pesticide contamination in three bird species of the Embalse La Florida water reservoir in the semiarid midwest of Argentina - Cid, Fabricio Damian (2007)
Organochlorine pesticides (OCs) have a variety of acute and chronic pathological effects on animals, are persistent in the environment and are accumulated in adipose tissue of animals. In Argentina there are few studies reporting the OC contamination in the fauna. Moreover, no data are available for an ecologically relevant region, the arid-semiarid midwest region of Argentina. Recently, it was reported OC contamination in the water of an important artificial water reservoir of this area, the Embalse La Florida in the San Luis province. The present study aims to provide OC baseline data for birds of Embalse La Florida and to evaluate the potential risk of OC contamination for the local avifauna. We selected two fish-eating species, Podiceps major (great grebe) and Phalacrocorax brasilianus (neotropic cormorant) and one omnivore species, Pitangus sulphuratus (great kiskadee) to evaluate OC contamination. α-, β-, δ- and γ-hexachlorocyclohexane (ΣHCH), p,p′-DDT, p,p′-DDD, p,p′-DDE and methoxychlor (ΣDDT), aldrin, dieldrin, endrin and endosulfan (ΣALD) and, cis-chlordane, trans-chlordane, heptachlor, heptachlor epoxide(ΣCHL) were measured in adipose tissue of two male great grebes, six neotropic cormorant (3 of each sex) and four great kiskadees (2 of each sex). We detected all OC pesticides assayed [ΣHCH range: ND to 3168.41 ng/g fat, ΣCHL range: ND to 4961.66 ng/g fat, ΣALD range: 287.07 to 9161.70 ng/g fat, ΣDDT range: 1068.98 to 6479.84 ng/g fat], with the exception of p,p′-DDT. Summed OC concentration in all bird species ranged from 2684.91 to 19231.91 ng/g fat. The omnivore had significantly greater concentrations of ΣCHLs than fish-eating species. Females of the neotropic cormorant had significantly higher amounts of ΣHCH and ΣCHL than males. The OC concentrations detected in birds were lower than those reported in the literature that are associated with deleterious effects on survival or reproduction in others species of birds. This study is the first report of OC contamination in birds of the midwest region of Argentina and constitutes a starting point for future studies that evaluate temporal changes of OCs in birds in this region.